An Overview of Wound Dressing Materials - Tânia Lagoa; Maria Cristina Queiroga; Luís Martins (MDPI AG, 2024)
Wounds are an increasing global concern, mainly due to a sedentary lifestyle, frequently associated with the occidental way of life. The current prevalence of obesity in Western societies, leading to an increase in type II diabetes, and an elderly population, is also a key factor associated with the problem of wound healing. Therefore, it stands essential to find wound dressing systems that allow for reestablishing the skin integrity in the shortest possible time and with the lowest cost, avoiding further damage and promoting patients' well-being. Wounds can be classified into acute or chronic, depending essentially on the duration of the healing process, which is associated withextent and depth of the wound, localization, the level of infection, and the patient's health status. For each kind of wound and respective healing stage, there is a more suitable dressing. The aim of this review was to focus on the possible wound dressing management, aiming for a more adequate healing approach for each kind of wound.